BUTTERFLIES OF GUNUNG HALIMUN-SALAK NATIONAL PARK, JAVA, INDONESIA, WITH AN OVERVIEW OF THE AREA IMPORTANCE - Djunijanti Peggie; Harmonis (Treubia, 2014)
Data on the occurrence of butterfly species at Gunung Halimun-Salak National Park is presented based on collections and observations obtained in 2004, 2007, 2009 and 2010. In total, 161 butterfly species (10 Hesperiidae, 23 Lycaenidae, 86 Nymphalidae, 17 Papilionidae, 21 Pieridae, and 4 Riodinidae) were recorded. Of the total number of species, 133 were recorded from Gunung Halimun and 82 were recorded from Gunung Salak. The occurrence of butterflies at this national park was compared with data known from other localities in Java. The significance of Gunung Halimun-Salak NP in terms of the butterfly diversity is discussed.